Circular economy as a direction for implementing the concept of sustainable development - Varvashenko, Vladyslav (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Міжнародні відносини, економіка, країнознавство, туризм, 2024)
The article states that the circular economy is an integral part of the concept of sustainable development. It is aimed at creating an economic system where resources are used as efficiently as possible, with minimal impact on the environment. In the context of sustainable development, the circular economy acts as an innovative approach to achieving economic, environmental and social sustainability. The subject of the study is the circular economy as a key element in achieving sustainable development goals. The aim of the article is to study the experience of European countries in the application of the circular economy model and to justify the need for the domestic economy to transition to sustainable development practices. The dialectical approach is fundamental in the research process. In addition, a systemic, comprehensive, interdisciplinary approach was used; the method of analyzing scientific publications; methods of qualitative and quantitative data analysis. The following results were obtained. A comparative analysis of linear and circular models of the economy was performed. The practice of implementing the basic principles of the circular economy in the activities of European countries was considered. Conclusions. Currently, Ukraine is actively implementing the principles of the circular economy, which are a key component of the European Green Deal. The European Union has provided Ukraine with several funding programs to support the transition to a circular economy model. However, despite the presence of important program documents and active movement towards the implementation of sustainable practices, Ukraine has not yet developed a comprehensive policy to support the circular economy. Given that our country has begun the process of negotiations on joining the European Union, it is advisable to take the principles of the European Green Deal as a basis for formulating decisions aimed at ensuring sustainable recovery. Particular attention should be paid to the principles of the circular transition of the national economy.